Synthesis of Chiral Spiro[oxindole-3,2′-pyrrolidine] Derivatives Integrated with Spiro Indane-1,3-dione and Trifluoromethyl Group Pharmacophores via Organocatalyzed Asymmetric [3+2] Annulation - Li, Fei; Li, Zhuo; Wang, Youming; Zhou, Zhenghong (Synthesis, 2023)
A mild and efficient organocatalyzed [3+2] cycloaddition of isatin-derived ketimines and 2-ylideneindane-1,3-diones has been realized. The resulting spiro[oxindole-3,2′-pyrrolidine]s bearing both a spiro indane-1,3-dione motif and a trifluoromethyl group were obtained in high yields with good diastereo- and enantioselectivities.
Keywords: asymmetric synthesis; indane-1,3-dione; isatin-based ketimine; organocatalysis; spiro[oxindole-3,2′-pyrrolidine]